Eschatological Interpretations of Mark 14:62 - Hollon, Elton L. (Neotestamentica, 2024)
The following article proposes three plausible eschatological interpretations of Mark 14:62, namely, proleptic, interwoven, and failed futurism. In support of the analysis, it draws together information from source, literary, and redaction criticism. It is argued that both the Old Testament and Similitudes support Mark's eschatological portrayal of the apocalyptic Son of Man because the saying takes several Old Testament intertexts and shares striking parallels with the Similitudes. The combination of Dan 7:13 and Ps 110:1 at Mark 14:62 and 1 En. 62:5-6 is particularly relevant. After presenting evidence for the eschatological interpretations, preterist objections assigning the saying's fulfilment to the first century CE are considered. Problems with the objections and historized interpretations are identified. In light of the parallels with the Similitudes, Mark 14:62 is judged more likely eschatological.